1995
DOI: 10.1080/00382167.1995.9629684
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Fluctuations and Diversity of Bark and Wood-boring Beetles in Lowland Forest: Implications for management Practices

Abstract: SYNOPSISThe phenology and diversity of wood-living beetles attacking Cedrela mexicana, Khaya nyasica and Milicia excelsa were observed for one year with weekly window-flight-trap collections. A total of 150 species (10 known to be common pests of timber) were collected, most of them occurring yearround and a few indicating seasonal fluctuations in abundance. The flight patterns and low catches depicted by some primary attackers could have some management implications in Kimboza or similar areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“… Schneider (1987) notes that more than one generation may inhabit the same gallery system, and describes the oral mycangia. Seasonal changes in numbers caught in traps have been related to temperature and rainfall in Africa ( Beaver and Löyttyniemi 1991 ; Madoffe and Bakke 1995 ), and in Central America ( Rangel et al 2012 ). Flight height preference in Amazonia is described by Abreu et al (2001) .…”
Section: Taxonomic Treatmentmentioning
confidence: 99%
“… Schneider (1987) notes that more than one generation may inhabit the same gallery system, and describes the oral mycangia. Seasonal changes in numbers caught in traps have been related to temperature and rainfall in Africa ( Beaver and Löyttyniemi 1991 ; Madoffe and Bakke 1995 ), and in Central America ( Rangel et al 2012 ). Flight height preference in Amazonia is described by Abreu et al (2001) .…”
Section: Taxonomic Treatmentmentioning
confidence: 99%
“…Anobiidae, Mycetophagidae, Languriidae, Nilitulidae and Cleridae) after commissioning of the plant needs further investigations to determine if their absence was due to habitat change as a consequence of the hydropower plant or due to other reasons, such as sampling artefact or seasonal variations (Zilihona 2003). It is well documented that there is great variation in arthropod abundance, richness and diversity in African rainforests between both seasons and years (Madoffe and Bakke 1995;Nummelin 1996). The results also indicated that Hydrophilidae, Meloidae and Carabidae provided convincing evidence regarding the effect of the hydropower plant, and therefore could be used as indicator groups for detailed monitoring studies in the Kihansi Gorge.…”
Section: Discussionmentioning
confidence: 66%
“…This is usually accomplished by flight, and since suitable breeding material may be patchily and irregularly distributed throughout the forest, its discovery may involve repeated flight over several days (Madoffe & Bakke 1995). Because of this behavior, it is possible to sample bark-and wood-boring insect populations using flight traps, with or without pheromone baits.…”
Section: Flight Trappingmentioning
confidence: 99%